International Graduate Students’ Academic Writing Practices in Malaysia: Challenges and Solutions - Mehar Singh, Manjet Kaur (Journal of International Students, 2015)
This article focuses on the challenges faced by non-native English speaking international graduate students in their academic writing practices while they studied at a university in Malaysia as well as the solutions they employed when faced with the challenges. Academic Literacies Questionnaire was used to collect data. Based on 131 participants, the findings indicate that non-native English speaking international graduate students faced challenges in their academic writing practices in the instructional settings where English was used as a medium. In addition, the results revealed that some challenges those students face were mainly attributable to the fact that English in Malaysia is not the native or first language. This study suggests policies and programmes to meet the unique academic writing background needs of these students and ensure their academic success.